BK Polyoma Virus Nephropathy Among Iranian Renal Transplant Recipients - Ghafari, A.; Lessan-Pezeshki, M.; Taghizadieh, M.; Rahimi, E. (Transplantation proceedings, 2008)
BK virus nephropathy (BKVN) is recognized as a cause of graft loss in renal transplant patients. The disorder may be related to the introduction of new, potent immunosuppressive regimens. We sought to assess the prevalence, outcome, and clinical characteristics of BKVN. We retrospectively analyzed 160 specimens from episode biopsies. BKVN was diagnosed by light microscopic examination and positive immunohistochemical staining. Among 160 patients, 21 (13.1%) were diagnosed as BKVN. The mean interval between biopsy and transplantation was 13.6 ± 10.67 months. There were no significant differences between BKVN patients and non-BKVN patients with respect to age, sex, interval between diagnosis and transplantation, cyclosporine blood level, and azathioprine versus mycophenolate mofetil immunosuppression. Graft loss occurred in 57.1% of BKVN versus 12.2% of non-BKVN subjects ( P = .005). There was a significant difference between antilymphocyte globulin (ALG)- and non-ALG-treated groups with respect to the incidence of BKVN (6.6% in non-ALG versus 19% in ALG groups; P < .01). BKVN was diagnosed by immunohistochemistry in 61% of specimens with acute rejection according to light microscopic evaluation. This is the first report of BKVN in Iranian renal allograft recipients. In our hospital, the prevalence of BKVN was higher than that previously reported for non-Iranian recipients. BKVN had a negative impact on graft survival.